A quantitative analysis of the efficiency of solar-driven water-splitting device designs based on tandem photoabsorbers patterned with islands of metallic electrocatalysts1. Issue 6 (3rd June 2015) - Chen, Yikai; Sun, Ke; Audesirk, Heather; Xiang, Chengxiang; Lewis, Nathan S.
<x xml:space="preserve">Abstract</x> Optical obscuration and kinetic overpotentials of patterned electrocatalyst films are investigated using a 0-dimentional load-line analysis and experimental measurements.